1965
DOI: 10.3758/bf03343512
|View full text |Cite
|
Sign up to set email alerts
|

Semantic satiation, forewarning, and decision latency

Abstract: Sixteen Ss were asked to decide if pairs of words had the same meaning. It was found that asking S to repeat one of the words 1 or 15 sec. in advance equally facilitated his decision. The results indicate thatforewarning and not semantic satiation reduces decision latency. Problem Fillenbaum (1964) has found that if S is asked to decide if two words have the same meaning, his decision is faster after repeating one of the words for 1 min. than after repeating an unrelated word. This would appear to be evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

1966
1966
1980
1980

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…In a similar experiment, Gumenik and Perlmutter (1966), found, in agreement with the results of Gough and Rohrman (1965), that repetition had no effect on decision latency.…”
Section: Number Of Elicited Associationssupporting
confidence: 74%
See 2 more Smart Citations
“…In a similar experiment, Gumenik and Perlmutter (1966), found, in agreement with the results of Gough and Rohrman (1965), that repetition had no effect on decision latency.…”
Section: Number Of Elicited Associationssupporting
confidence: 74%
“…This study, and Fillenbaum's explanation of his findings, have been reviewed and criticized elsewhere (Esposito & Pel ton, 1969). Gough and Rohrman (1965) designed a study in which amount of repetition (1 or 15 seconds) of the satiator word, decision-pair relationship (synonym or unrelated), and amount of practice were varied. They found that giving subjects one of the words of the decision pair as a "satiator" word before they decided if the words of the decision pair were synonymous (the "forewarning" condition) yielded significantly shorter latencies than did using a "satiator" word unrelated to the decision pair.…”
Section: Number Of Elicited Associationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several eXperiments (Fillenbaum, 1964;Gumenik & Perlmutter, 1965;Gough & Rohrman, 1965) have shown that if someone is asked to decide if a pair of words are synonyms, his decision is greatly facilitated if he is given one of the words in advance. This paper reports two experiments concerned with the explanation of this forewarning effect.…”
mentioning
confidence: 99%
“…This paper reports two experiments concerned with the explanation of this forewarning effect. In a previous paper (Gough & Rohrman, 1965) the following explanation was suggested: To compare two words and decide if they have the same meaning, S must compare their meanings. To compare their meanings S must first retrieve them, and it can be assumed that this retrieval process occupies some measurable duration.…”
mentioning
confidence: 99%